Association of risk management practices and financial performance of microfinance institutions in Ethiopia: A two-step system generalized method of moments approach - Megbaru Tesfaw Molla; Ratinder Kaur (PLoS ONE, 2025)
This study aims to analyze the relationship between risk management and performance of microfinance institutions (MFIs) in Ethiopia. An explanatory research design was employed by collecting secondary data from the financial statements of 24 sample MFIs from 2013/2014–2022/2024. The study utilized STATA version 15 software to address dynamic endogeneity bias, unobserved heteroskedasticity, and autocorrelation within individual units’ errors in dynamic panel data using the generalized method of moments (GMM) estimator. According to the results of this study, both lagged variables, namely return on assets and return on equity, have a positive effect on the financing performance of Ethiopian MFIs. Financial leverage, interest rate risk, and cash-to-total deposits are negatively related to MFIs’ returns on assets and return on equity. The relationship between loan loss provisions, loans and advances, and returns on assets is negative and significant but not with returns on equity. Loan-to-deposit ratios are positively related to financial performance indicators, but nonperforming loans are not significantly related to performance indicators. Thus, this study highlights strategies to enhance the financial performance and sustainability of Ethiopian MFIs. To do so, policymakers should foster an enabling environment for MFIs through financial literacy, risk management, and addressing financial challenges. In addition, MFI managers should focus on profitability, liquidity optimization, and effective credit evaluation to enhance performance.